Model-based Simulation of VoIP Network Reconfigurations using Graph Transformation Systems - Khan, Ajab; Torrini, Paolo; Heckel, Reiko (Electronic Communications of the EASST, 2009)
We address the modelling and validation of P2P networks with special attention for problems related to VoIP services, focusing particularly on Skype. We use generalised stochastic graph transformation systems and associated stochastic simulation techniques based on generalised semi- Markov processes.